Social policy towards demographic changes in European countries – examples of solutions and an assessment of their effectiveness - Kacprowska, Krystyna (Civitas et Lex, 2023)
According to David Gill, social policies are courses of action aimed at influencing the general quality of life in a society, the circumstances of life of individuals and groups in this society, as well as the nature of intra-social relations between individuals, groups, and society. Antoni Rajkiewicz defines social policy as “the sphere of activity of the state and other public bodies and social forces that deals with shaping the living conditions of the population and interpersonal relations (especially in the living and working environment)”. The term “demographic change” describes the age structure of the population adapting to changes in living conditions. Consequently, changes in the composition of the age structure of society are the result of social changes. When analyzing the EU population pyramids, we can see that the first two decades after World War II were characterized by a particularly high birth rate. Since the 1970s, demographers have noted negative trends in the structure of Europe’s population. The lower birth rate in the recent past and present is associated with an increase in the life expectancy of Europeans. Persistently low birth rates lead to an aging population if mortality rates remain low. Consequently, half of the population growth in Europe between 2005 and 2050 will not be due to births, but to more people living longer. The work was written to present and evaluate social policy instruments implemented as a response to the ongoing demographic changes in European countries.